1996
DOI: 10.1097/00005344-199601000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrochlorothiazide on the Pharmacokinetics of Enalapril in Hypertensive Patients with Varying Renal Function

Abstract: An open, randomised, cross-over study was performed to investigate the pharmacokinetics of enalaprilat, administered as 20 mg enalapril both as monotherapy and in combination with hydrochlorothiazide (HCTZ 12.5 mg). Three groups of 6 hypertensive patients were enrolled [untreated diastolic blood pressure (DBP) 90-115 mm Hg]; normal renal function [glomerular filtration rate (GFR) > 81 ml min-1 1.73 m-2], mild renal impairment (GFR 51-80 ml min-1 1.73 m-2), and moderate renal impairment (GFR 31-50 ml min-1 1.73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
2
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…A similar finding was reported by Hersh et al. , who compared enalapril pharmacokinetics and blood pressure response in hypertensive patients with no, mild or moderate renal impairment [14].…”
Section: Discussionsupporting
confidence: 85%
“…A similar finding was reported by Hersh et al. , who compared enalapril pharmacokinetics and blood pressure response in hypertensive patients with no, mild or moderate renal impairment [14].…”
Section: Discussionsupporting
confidence: 85%
“…This administration and at 1 and 2 h following administration. Otherwise subjects were fasting from 8 h before until 4 h result was also found in one study with enalapril/HCTZ [7], but, in another study, the level of enalaprilat achieved after drug administration. Blood samples for determination of fosinoprilat and HCTZ concentration and for ACE was increased significantly when enalapril was administered following HCTZ independent of the degree of activity and cumulative urine collections were obtained before and up to 24 h (day 1) or 48 h (day 5) after renal impairment [8].…”
supporting
confidence: 52%
“…and a decrease in urinary elimination at lower rates of GFR which correlated predictably with the degree of The pharmacokinetic results showed there were no clinically significant differences between the renally renal impairment [7]. Another study, however, found that the administration of enalapril with HCTZ was impaired patients and the normal subjects.…”
mentioning
confidence: 85%
See 1 more Smart Citation